Business Strategy Sixtrees 2022-2023 - Kevin Rousul; Aprihatiningrum Hidayati (Business Review and Case Studies, 2022)
The fashion industry is growing rapidly along with technological developments so that it is able to support Indonesia's economic growth. However, at the start of the pandemic, this industry experienced a slowdown due to decreased purchasing power. Sixtrees as a new local fashion brand has also been affected. Since 2021, Sixtrees has stopped operating due to limited capital. Future analysis and development of the Sixtrees brand business strategy are required. The purpose of this study was to identify the weaknesses, strengths, opportunities, and threats of Sixtrees and to develop alternative strategies to be implemented from 2022 to 2023. The survey was conducted by distributing online questionnaires to collect data from 100 respondents who are fashion enthusiasts. The analysis was carried out by examining the company's external and internal factors and alternative business strategies were obtained using SWOT analysis and the TOWS matrix. The results of the study show that the company is still behind compared to its competitors, so it is necessary to implement alternative strategies in order to gain opportunities and minimize existing risks. Sixtrees needs to strengthen product and digital marketing advantages in order to reach a wider market and achieve profitability. Keywords: business strategy, fashion, online, SWOT analysis, TOWS matrix